Ending Holy Wars: religion and conflict resolution in civil wars - Svensson, Isak (New approaches to peace and conflict, 2012)
Front Cover; Author biography; Other titles in UQP's New Approaches to Peace and Conflict series; Title page; Imprint page; Dedication; Note from Series Editor; Contents; List of tables and graphs; Preface; Introduction; Chapter 1 - Where and when do religious conflicts occur?; Chapter 2 - Which religious conflicts are difficult to resolve?; Chapter 3 - How do religious issue conflicts get resolved through peace agreements?; Chapter 4 - How do religious issue conflicts get resolved through concessions?; Chapter 5 - Towards a theory of desacralisation; Chapter 6 - Implications. - AcknowledgementsNotes; References; Index. - An exploration of how religious dimensions affect the possibilities for conflict resolution in civil war, this account systematically attempts to map out the religious dimensions of internal armed conflicts and to explain the conditions under which religious dimensions impede peaceful settlement. Drawing upon empirical work on global data, and based on the Uppsala Conflict Data Program, this book shows how religious identities and incompatibilities influence the likelihood of agreements and the mechanisms through which parties and third-party me